The awareness of having a family history of hearing problems and the impact on those with hearing difficulties themselves: a questionnaire. - Kramer SE; Stephens D; Espeso A (Audiological Medicine, 2006)
In the recent past, the number of studies on genetic aspects of hearing loss has risen rapidly. Despite this, the specific impact of the family history of hearing loss on those having hearing loss themselves is still a relatively unexplored area of research. This study investigates the impact of a family history of hearing loss in relation to awareness of that history. The aim was to empirically identify the number and the nature of the underlying constructs in the domain of family history of hearing loss. A structured 20-item questionnaire was designed. Responses were obtained from 192 adults with late onset non-syndromal hearing loss. The ages ranged from 17 to 92 years (mean 60.4 years, SD 13.9). An exploratory factor analysis was performed and the psychometric features of the scales were examined. Multiple regression analyses were performed to investigate the association between the impact of a family history of hearing loss and the awareness of that history, demographic variables and audiometric measures. Factor analyses confirmed the existence of two main factors: role modelling, distress and concern; and three minor factors: distress from hearing loss per se, importance of own hearing loss and distinctiveness of individual hearing. Awareness of family history was significantly associated with role modelling. Severity of hearing loss was significantly related to distress and concern. The results are discussed in terms of the themes identified, the utility of the questionnaire and the utility of family history and role-modelling in clinical care. The concept of family history of hearing loss and making people aware of it by identifying and introducing suitable role models deserves further attention both in research and in clinical practice.